Minocycline-Loaded Titanium Dioxide Nanoparticles for Augmented Synergistic Periodontal Sonodynamic Chemotherapy - Huang S; Xia C; Zuo W; Wang R; Xu N; Ye W; Li X; Chen Y; Zhu X (International Journal of Nanomedicine)
Shuying Huang,1,2,* Chengyao Xia,3,* Wenbao Zuo,3 Rui Wang,2 Nuo Xu,2 Wenxin Ye,2 Xiao Li,2 Yong Chen,2 Xuan Zhu3 1Xiamen University School of Public Health, Xiamen, People’s Republic of China; 2Department of Stomatology, School of Medicine, Xiamen University, Xiamen, People’s Republic of China; 3Fujian Provincial Key Laboratory of Innovative Drug Target Research, School of Pharmaceutical Sciences, Xiamen University, Xiamen, 361102, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Chen, Email yongchen@xmu.edu.cn Xuan Zhu, Email zhuxuan@xmu.edu.cnBackground: The current clinical treatment of periodontitis usually involves mechanical removal of pathogenic bacteria through ultrasonic scaling and root planing, supplemented with antibacterial medications to inhibit microbial overgrowth. However, the therapeutic efficiency remains unsatisfactory due to complicated periodontal anatomy, limited plaque removal, short retention of antibiotics, and related side effects.Methods and Results: To address these issues, we successfully synthesized mesoporous titanium dioxide nanoparticles (MTN) via a sol-gel method, which were modified with hemoglobin (Hb) and loaded with minocycline (MINO). The resulting Hb-MTN/MINO nanoparticles had a size of 215 nm, zeta potential of − 19.8 mV± 0.9 mV, and uniform shape with a PDI index of 0.176. The modification with hemoglobin (Hb) provided sufficient oxygen for antimicrobial sonodynamic therapy (aSDT), contributing to improved generation of reactive oxygen species (ROS) under low ultrasound intensity. After MINO loading, the system exhibited notable antibacterial efficacy, with a 6 log reduction of bacterial counts compared to the control group. Hb-MTN/MINO was evaluated in vivo in terms of oral index, soft and hard tissues, along with biosafety evaluation in periodontal disease model rats. Hb-MTN/MINO demonstrated a satisfactory therapeutic effect, whereby the periodontal condition of the rats exhibited a greater improvement than the control group, and measurement of the serum levels of inflammatory factors revealed that both IL-6 and MMP-9 were significantly downregulated.Conclusion: These findings confirm the potential of Hb-MTN/MINO nanoparticles as a promising treatment option for periodontitis.Keywords: periodontitis, nanoparticles, sol-gel method, sonodynamic therapy, minocycline